Estudo da influência do BaO na bioatividade e radiopacidade de vidros borofosfatos para regeneração óssea e para aplicações em blindagem de radiação ionizante - LIMA, Ailda da Luz (2022)
In this work, the effect of replacing P2O5 and B2O3 by BaO in borophosphate glasses of the system was investigated (40 − x/2)B2O3 − (25 − x/2)P2O5 − 7CaF2 − 20Na2O − 8CaO − xBaO (x=0, 5, 7,5 e 10 mol%), in the physical properties, radiopacity and bioactive properties of these glasses. The work was divided into two phases: in phase 1, the samples were synthesized by the fusion/cooling method, characterized by radiography for the choice of which network modifier would be used in the study. In phase 2, the samples were synthesized by the same method, submitted to bioactivity test in SBF for 28 days and characterized by x-ray diffraction, radiography, density and molar volume, Fourier transform infrared spectroscopy, differential scanning calorimetry, ionizing radiation shielding and optical absorption coefficient. The increase in BaO concentration caused an increase in the values obtained for density, reduction of molar volume, no significant changes in glass transition temperatures and crystallization temperature with the increase of bao content. The radiography performed in comparison to the gray levels of the penetrometer, by converting the pixel into units of measurement, show that there are similarities between the density of 1 mm of glass (sample with 0% of BaO), 1mm of aluminum (mmEq/Al) and 1mm of dentin (mmEq/Al). However, samples with 5;7.5 and 10% BaO are equivalent to 1.68; 2.29 and 2.90 mmEq/Al, respectively, with the same thickness. For shielding ionizing radiation in the low energy region of X-rays (60KeV), attenuation is remarkably increased with the BaO content and reaches a value of up to 16 times that of common concrete for the sample with 10% BaO. The optical absorption spectra presented a window of wide transparency. The pH measurements were performed daily, deevidenced the decrease in the pH of the SBF solutions for all immersed samples. The diphrates of the samples before immersion were amorphous and after immersion showed hydroxyapatite and fluorapatite peaks. Fourier transform infrared spectroscopy spectroscopy, before immersion, indicated structural changes in the glasses with the addition of BaO and after immersion in SBF exhibited absorption bands in the regions attributed to phosphates, characteristic of apatite.